BREAKING THE SILENCE: UTILIZING PECHA KUCHA TO PROMOTE STUDENTS SPEAKING SKILLS - Mahendra, Aloisius Wisnu (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
This study aims to report the utility of Pecha Kucha in promoting students speaking skills in the general English course. As English known as the international language for communication, Indonesians expect to master English in order to broaden their future career opportunities. Most of them seek for English courses providing various communicative activities with the hope that they can improve and sharpen their speaking skills. Although the course has been designed for communication purpose, some students still are not be able to express their ideas freely during the speaking activities. They may feel afraid of making grammatical errors resulting to their low speaking performance. To facilitate students learning and encourage them to practice their speaking skills, Pecha Kucha has been utilized during the course. The study was conducted in the Language Institute of Sanata Dharma University in 2017. Recorded learning activities utilizing Pecha Kucha and field notes were collected through the classroom teaching-learning practices. Semi-structured interviews were also conducted to explore the findings and the analysis. The findings shows that the students actively engage with the utilization of Pecha Kucha by being able to explore their ideas and practice their speaking skills, and enjoy the learning process eventually.